Integrated prevention and management of non-communicable diseases, including musculoskeletal health: a systematic policy analysis among OECD countries - Andrew M Briggs; Samantha Bunzli; Jennifer G Persaud; Marie L Deverell; Brigitte Tampin; Yuka Sumi; Olav Amundsen; Elizabeth MG Houlding; Anontella Cardone; Thora Hugosdottir; Sophia Rogers; Miklós Pozsgai; et al. (BMJ Global Health)
Introduction Development and implementation of appropriate health policy is essential to address the rising global burden of non-communicable diseases (NCDs). The aim of this study was to evaluate existing health policies for integrated prevention/management of NCDs among Member States of the Organisation for Economic Co-operation and Development (OECD). We sought to describe policies’ aims and strategies to achieve those aims, and evaluate extent of integration of musculoskeletal conditions as a leading cause of global morbidity.Methods Policies submitted by OECD Member States in response to a World Health Organization (WHO) NCD Capacity Survey were extracted from the WHO document clearing-house and analysed following a standard protocol. Policies were eligible for inclusion when they described an integrated approach to prevention/management of NCDs. Internal validity was evaluated using a standard instrument (sum score: 0–14; higher scores indicate better quality). Quantitative data were expressed as frequencies, while text data were content-analysed and meta-synthesised using standardised methods.Results After removal of duplicates and screening, 44 policies from 30 OECD Member States were included. Three key themes emerged to describe the general aims of included policies: system strengthening approaches; improved service delivery; and better population health. Whereas the policies of most countries covered cancer (83.3%), cardiovascular disease (76.6%), diabetes/endocrine disorders (76.6%), respiratory conditions (63.3%) and mental health conditions (63.3%), only half the countries included musculoskeletal health and pain (50.0%) as explicit foci. General strategies were outlined in 42 (95.5%) policies—all were relevant to musculoskeletal health in 12 policies, some relevant in 27 policies and none relevant in three policies. Three key themes described the strategies: general principles for people-centred NCD prevention/management; enhanced service delivery; and system strengthening approaches. Internal validity sum scores ranged from 0 to 13; mean: 7.6 (95% CI 6.5 to 8.7).Conclusion Relative to other NCDs, musculoskeletal health did not feature as prominently, although many general prevention/management strategies were relevant to musculoskeletal health improvement.